Using online social networks to provide a parental health-education intervention for preventing unintentional injuries among children aged 0–3 years: A randomized controlled trial and social network analysis in Shanghai, China - Feng, Yuheng; Li, Xiaohong; Ma, Xueqi; Zhu, Zhixu; Chen, Kaiyue; Gao, Jun; Xia, Jingwei; Jiang, Ruo; Lu, Jun (Frontiers in Public Health, 2023)
Unintentional injury among children represents a major public health problem. Online-social-network-based parental-health-education is a potential way to reduce child unintentional injuries. The study aimed to explore the mechanisms by which online-social-network-based health education may reduce the unintentional injuries among children aged 0–3 years. We conducted a participant-blinded, randomized controlled, online-social-network-based health-education intervention study from March 2019 to February 2020 in Shanghai. We established four WeChat groups (two intervention groups and two control groups). For the intervention groups, a doctor’s assistant regularly delivered information regarding unintentional injuries among children, and community childcare doctors answered parents’ questions concerning their children’s health, including unintentional injuries. Meanwhile, the control groups did not receive any information from the assistant. The study selected one intervention group and one control group and compared the ego network and whole network indicators to determine the differences between the intervention and control groups. In the intervention and control groups, 64.5% and 31.9% of the members, respectively, engaged in communication, and 1,736 and 273 records, respectively, were obtained. Regarding ego network, the doctor showed the largest network in the intervention group, and the size of the intervention group’s network was twice that of the control group; the number of ties in the intervention group was nine times that of the control group. Fourteen and four parents in the intervention and control group played an active role, respectively. Regarding centrality, all WeChat groups were loose and multiple centers existed. Regarding subgroup cohesion, the intervention group had 28 cliques with 27 members, and the control group had 4 cliques with 4 members. For structural hole, 23.7% and 7.5% members in the intervention and control group actively participated in interactions, respectively, having strong control and influence over other parents; 69.2% and 59.1% members in the intervention and control group, respectively, had values of <1.000, showing that they had strong ability to cross-jump structural holes. Online-social-networks-based health education interventions could enhance communication among parents, and between parents and community childcare doctors, and also shorten the social distance between them. Thus, online-social-network-based parental-health-education-intervention can be a feasible and generalizable means of preventing unintentional injuries among children.